Perang Dagang AS-Cina : Dampak Ekonomi Pada Negara Mitra Dagang AS-Cina - Mutiara Sari; Marselina Marselina; Neli Aida (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
Trade between countries has a positive impact on each country in meeting their needs and obtaining profits, but the increase in trade activities has also led to trade competition. This causes relations between countries not always run well, thus triggering conflicts between countries, namely trade wars. The trade war that is currently happening is between the United States and China through trade tariffs. This will have an impact on the economic growth of both trading partner countries.The purpose of this study is to analyze the impact of the US-China trade war on economic growth in 10 US-China trading partner countries before and after the US-China trade war. In this study, quantitative analysis of panel data regression was used. Based on the results of panel data regression, it was known that the US-China trade war had an impact on economic growth in 10 US-China trading partner countries. In addition, the export performance variable had a positive and significant impact on economic growth in 10 US-China trading partner countries before and after the US-China trade war. The FDI variable had no significant effect on economic growth in 10 US-China trading partner countries. The US-China trading partner countries were expected to reduce their dependence on the United States and China.